Differences Between Students’ and Teachers’ Fairness Perceptions: Exploring the Potential of a Self-Administered Questionnaire to Improve Teachers’ Assessment Practices - Sonnleitner, Philipp; Kovacs, Carrie (Frontiers in Education, 2020)
The ability to assess learning outcomes is vital to effective teaching. Without understanding what students have learned, it is impossible to tailor information, tasks or feedback adequately to their individual needs. Thus, assessment literacy has been increasingly recognized as a core teacher competency in educational research, with many empirical studies investigating teachers’ abilities, knowledge and subjective views in relation to classroom assessment. In contrast, relatively few studies have focused on students’ perspectives of assessment. This is surprising, since gathering students’ feedback on their teachers’ assessment practices seems a logical step toward improving those practices. To help fill this gap, we present an explorative study using the recently developed Fairness Barometer as a tool to help identify specific strengths and weaknesses in individual teachers’ assessment methods. Viewing assessment through the lens of classroom justice theory, the Fairness Barometer asks students and teachers to rate aspects of procedural and informational justice in their own (teachers’) assessment practices. We examined the resulting fairness discrepancy profiles for 10 Austrian secondary school classes (177 students). Results showed wide variation in profile pattern, evidence that both students and teachers can differentiate between different aspects of assessment fairness. Further exploration of the resulting discrepancy-profiles revealed certain problem types with some teachers differing from their students’ perception in almost every rated aspect, some showing specific assessment-related behaviors that require improvement (e.g. explaining grading criteria of oral exams), and others demonstrating almost identical responses as their students to the addressed fairness aspects. Results clearly indicate the potential of the Fairness Barometer to be used for teacher training and teacher self-development within the domain of teacher assessment literacy.